NORTHERN MALI 2012: THE SHORT-LIVED TRIUMPH OF IRREDENTISM (The Strategic Review for Southern Africa, 2020)
Strengthened by weapons from Libya, the rebellion beginning in Mali incJanuary 2012 finally gave a Tuareg-dominated irredentist movement control of Northern Mali in the fourth rebellion since independence. The Movement for the National Liberation (MNLA) called this area Azawad, proclaiming it as independent. Although it was to be a multiethnic country, the MNLA remained dominated by the Tuareg. Discontent among Malian officers during the fight against the rebels produced a coup d'état, undermining the military command structure, which greatly contributed to the rebels' success. An unavowed alliance existed with AQIM (Al-Qaida of the Islamic Maghreb) and the Tuareg Islamist group Ansar Dine. The latter and the AQIM-offshoot, MUJAO (the Movement for Unity and Jihad in West Africa), eventually drove the MNLA from Northern Mali. Increasingly, the Islamists imposed an extreme version of sharia, adding to the mass flight of refugees. Negotiations between the interim Malian government, the MNLA and the Ansar Dine still continued until the latter and AQIM moved towards Southern Mali. The perceived threat made the Malian government request French assistance. The intervention gradually drove the Islamists from the country, enabling the restoration of the state in Northern Mali. The conflict reveals underlying features of the political situation in Northern Mali, and highlights how the Tuareg and NorthernMalians have responded to the state's shortcomings through rebellion. Access to the state passes through privileged individuals. Rebels have been drawn closer to the state after conflicts, with only some benefitting from this arrangement. This is mirrored at a local level, with public figures and their followers enjoying the closest relation to the state. Producing widespread discontent, this situation is marked by insecurity because of a weak state presence. Misgivings have fed into new rebellions. Weak state control also allowed the AQIM to engage in hostage taking and for smuggling to expand. This volatile situation produced the latest rebellion. An improved connection to the state for Northern Mali and a strong state presence are necessary to counteract the factors responsible for repeated conflict.